Adsorption of cadmium ion from water by using non-toxic iron oxide adsorbent; experimental and statistical modelling analysis - Gusain D.; Sahani S.; Sharma Y.C.; Han S.S. (My University, 2025)
To maintain a safe and healthy environment, non-toxic adsorbents must be discovered to remove contaminants from water. A non-toxic nano iron oxide adsorbent was synthesized and used in this study to investigate the removal of Cd ions from an aqueous solution. Adsorption variables such as pH, initial Cd ions concentration, and adsorbent dosage were optimized through response surface methodology using the Box-Behnken design. Optimum conditions were found at an adsorbent dose of 4 gL−1 and an initial Cd ions concentration of 27 mg/L at pH 7. Langmuir isotherm and pseudo-second-order models fit the experimental data better. Linear analysis is a preferential method for determining isotherm data. It was discovered that the adsorbent had a maximum adsorption capacity of 5.89 mg/g. Cd ions adsorption by nano iron oxide adsorbent was found to be spontaneous and endothermic using both linear and non-linear approaches (enthalpy: 36.28 kJ/mol). The Cd ions removal process proceeded with a decrease in entropy (0.1796 kJ/mol), and the Gibbs free energy values ranged from − 27.58 to − 36.35 kJ/mol. The Langmuir constant method is preferred over the partition method in the estimation of thermodynamic parameters. © The Author(s) under exclusive licence to Iranian Society of Environmentalists (IRSEN) and Science and Research Branch, Islamic Azad University 2024.